Lysing Patterns of Retracted Blood Clots with Diffusion or Bulk Flow Transport of Plasma with Urokinase into Clots – a Magnetic Resonance Imaging Study In Vitro - Blinc, A; Keber, D; Lahajnar, G; Stegnar, M; Zidanšek, A; Demsar, F (Thrombosis and Haemostasis, 1992)
Fresh retracted clots are known to be poorly lysable by fibrinolytic agents. We have studied whether lysis of retracted clots could be enhanced by bulk transport in comparison to pure diffusion of plasma containing urokinase (400 IU/ml) into the clots. Cylindrical retracted blood clots were occlusively glued by a polyester into plastic tubes and put in contact with plasma through the clot bases. One group of clots (perfused clots, n = 10) was placed under a pressure difference of 6 kPa (60 cm H20) which resulted in an average plasma flow of 0.97 ± 0.34 µl/min through the clot during the first hour. Another group of clots (non-perfused clots, n = 10) was incubated in the lytic plasma without a pressure difference. Clot sizes were measured during lysis by magnetic resonance imaging (MRI). Channels representing lysed areas penetrated into perfused clots with a velocity of 5.4 ± 1.6 mm/h (n = 10), whereas the boundaries of non-perfused clots subsided with a velocity of less than 0.1 mm/h. Eight of the 10 perfused clots were recanalized after 8 h and the sizes of the perfused group were reduced to 64.0 ± 10.7% of the initial values. The relative sizes of non-perfused clots after 8 h remained significantly higher: 95.0 ± 1.3%, p <0.005. In a separate experiment good agreement was obtained between the measured clot sizes by MRI and the residual radioactivity of 125I-fibrin in the clot. The strong dependence of lysis on the transport mechanism of plasma with urokinase into retracted clots suggests that local hemodynamic conditions in vivo are likely to influence the lysis of thrombi.